Non-relativistic spectrum of two-color QCD at non-zero baryon density - Simon Hands (Physics Letters B, 2012)
The heavy quarkonium spectrum of Two Color QCD (QC_2D) at non-zero quark chemical potential mu and temperature T with mu/T>>1 has been calculated in both S- and P-wave channels using a lattice non-relativistic formulation of QC_2D. As mu is varied, the quarkonium spectra reveal three separate regions, corroborating previous findings that there are three distinct physical regimes of QC_2D at low temperature and high baryon density: hadronic matter, quark/quarkyonic matter, and deconfined matter. The results are interpreted in terms of the formation of heavy-light Qq states in the two-color baryonic medium